The impact of environmental factors in severe psychiatric disorders - Schmitt, Andrea; Malchow, Berend; Hasan, Alkomiet; Fallkai, Peter (Frontiers in Neuroscience, 2014)
During the last decades, schizophrenia has been regarded as a developmental disorder. The neurodevelopmental hypothesis proposes schizophrenia to be related to genetic and environmental factors leading to abnormal brain development during the pre- or postnatal period. First disease symptoms appear in early adulthood during the synaptic pruning and myelination process. Meta-analyses of structural MRI studies revealing hippocampal volume deficits in first-episode patients and in the longitudinal disease course confirm this hypothesis. Apart from the influence of risk genes in severe psychiatric disorders, environmental factors may also impact brain development during the perinatal period. Several environmental factors such as antenatal maternal virus infections, obstetric complications entailing hypoxia as common factor or stress during neurodevelopment have been identified to play a role in schizophrenia and bipolar disorder, possibly contributing to smaller hippocampal volumes. In major depression, psychosocial stress during the perinatal period or in adulthood is an important trigger. In animal studies, chronic stress or repeated administration of glucocorticoids have been shown to induce degeneration of glucocorticoid-sensitive hippocampal neurons and may contribute to the pathophysiology of affective disorders. Epigenetic mechanisms altering the chromatin structure such as histone acetylation and DNA methylation may mediate effects of environmental factors to transcriptional regulation of specific genes and be a prominent factor in gene-environmental interaction. In animal models, gene-environmental interaction should be investigated more intensely to unravel pathophysiological mechanisms. These findings may lead to new therapeutic strategies influencing epigenetic targets in severe psychiatric disorders.